Aryl diazonium modification for improved graphite fibre brush in microbial fuel cell - Siti Farah Nadiah Rusli; Mimi Hani Abu Bakar; Seratul Jemiah Abdul Rani; Loh, Kee Shyuan; Mohd Shahbudin Mastar (Penerbit Universiti Kebangsaan Malaysia, 2018)
Aryl diazonium salts are coupling agents that assist in molecules attachment to interfaces for sensing purposes. Despite not being fully explored and not yet widely applicable for cell-based sensors, the high stability of aryl diazonium salt formed sensing system is highly favorable in biological applications. Carbon-based electrodes are the most commonly used in aryl diazonium modification due to its post grafting stable C-C bond formation. Here, salt bridge based microbial fuel cells (MFCs) were used to study on the effect of aryl diazonium modification on the anode graphite fibre brush. Aryl diazonium salts were in situ generated by the diazonation of p-phenylenediamine with NaNO2 in HCl solution. The electrochemical performance of the aryl diazonium modified graphite brush MFC was measured and compared with the unmodified graphite brush MFC. The power output of the modified graphite brush bioanode was higher (8.33 W/m3) than the unmodified graphite brush (7.60 W/m3) after 20 days of operation with ferricyanide as the catholyte. After 70 days of operation using phosphate buffer solution as the catholyte, the Pmax of modified brush was three times higher (0.06 W/m3) than of the unmodified brush (0.02 W/m3), which indicates an enhanced binding towards the substrate that facilitates a better electron transfer between the microbial and electrode surface.